Effect of Tik-Tok and Leaflet Media in Increasing Adolescents’ Knowledge and Attitude About Reproductive Health - Haninuna, Gilbert Yesaya; Nayoan, Christina Rony; Haba Bunga, Eryc Z (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2023)
Introduction: The lack of information about reproductive health obtained by adolescents can lead to the inability of adolescents to maintain their reproductive health. Media could be used to improve knowledge and attitudes. It is important to deliver health education using attractive media to influence adolescents’ understanding and attitudes about reproductive health. This study employed a new media, Tik-Tok to improve adolescents’ reproductive health knowledge and attitude. This study is aimed to compare the effectiveness of using Tik-Tok and leaflets on increasing adolescents' knowledge and attitudes in East Nusa Tenggara, IndonesiaMethods: This research was a quasi-experimental study, with a